Pharmacological modulation of vascular ageing: A review from VascAgeNet - Roth, Lynn; Dogan, Soner; Tuna, Bilge Guvenc; Aranyi, Tamas; Benitez, Sonia; Borrell-Pages, Maria; Bozaykut, Perinur; De Meyer, Guido R Y; Duca, Laurent; Durmus, Nergiz; Fonseca, Diogo; Fraenkel, Emil; et al. (Ageing research reviews, 2023)
Vascular ageing, characterized by structural and functional changes in blood vessels of which arterial stiffness and endothelial dysfunction are key components, is associated with increased risk of cardiovascular and other age-related diseases. As the global population continues to age, understanding the underlying mechanisms and developing effective therapeutic interventions to mitigate vascular ageing becomes crucial for improving cardiovascular health outcomes. Therefore, this review provides an overview of the current knowledge on pharmacological modulation of vascular ageing, highlighting key strategies and promising therapeutic targets. Several molecular pathways have been identified as central players in vascular ageing, including oxidative stress and inflammation, the renin-angiotensin-aldosterone system, cellular senescence, macroautophagy, extracellular matrix remodelling, calcification, and gasotransmitter-related signalling. Pharmacological and dietary interventions targeting these pathways have shown potential in ameliorating age-related vascular changes. Nevertheless, the development and application of drugs targeting vascular ageing is complicated by various inherent challenges and limitations, such as certain preclinical methodological considerations, interactions with exercise training and sex/gender-related differences, which should be taken into account. Overall, pharmacological modulation of endothelial dysfunction and arterial stiffness as hallmarks of vascular ageing, holds great promise for improving cardiovascular health in the ageing population. Nonetheless, further research is needed to fully elucidate the underlying mechanisms and optimize the efficacy and safety of these interventions for clinical translation.
Keywords: Arterial stiffness; Oxidative Stress; signální transdukce; Signal Transduction; Pharmacology; Vascular ageing; Endothelial dysfunction; Cellular Senescence; oxidační stres; stárnutí; Humans; Vascular Stiffness; Dietary supplements; Drugs; lidé; Aging; stárnutí buněk; tuhost cévní stěny